Comparative Study Of Whole-Body Vibration Exposure Between Train And Car Passengers: A Case Study In Malaysia - Ahmad Rasdan, Ismail; M.Z., Nuawi; N.F., Kamaruddin (Universiti Malaysia Pahang, 2011)
Train and car are the important transportations in the whole world. In highly developed countries, train becomes essential for human usage as the most well-known public transportation, whereas car plays a significant role for the human to travel from one place to the other place promptly. High magnitude of vibration formed by the train and car may cause diseases and health problems to the human especially a low back pain.The aim of this study was to evaluate and validate the values of daily exposure to vibration A(8) and vibration dose value (VDV) exposed to the passengers travelling in the train and car and the effects produced by the exposure towards human body, moreover all at once to introduce a newly developed whole-body vibration measurement instrumentation. One national train travelled from East Coast to the South has been chosen to conduct the study. The whole-body vibration exposure was measured in 8 hours, which is equal to the duration for normal occupation condition. One national car has been picked randomly and the exposure was measured in 5 min and 10 min respectively. All the data was computed by using IEPE(ICPTM) accelerometer sensor connected to DT9837 device which is capable to measure and analyze vibration effectively. The vibration results attained were displayed in personal computer by using custom graphical user interface (GUI). Matlab software was used to interpret the data obtained. From the results shown, the whole-body vibration exposure level can be determined. It can be concluded that the whole-body vibration absorbed by human body enhanced when the magnitude of vibration exposure experienced by the passengers increased. This can be proved by the increasing of the value of daily exposure to vibration A(8) and VDV calculated in the study.